Diode Laser Stapedotomy vs Conventional Stapedotomy in Otosclerosis: A Double-Blinded Randomized Clinical Trial. (June 2016) - Parida, Pradipta Kumar; Kalaiarasi, Raja; Gopalakrishnan, Surianarayana
Objectives: To assess and compare the efficacy of diode laser stapedotomy (DLS) and conventional manual stapedotomy (CMS) in the treatment of otosclerosis. Study Design: Randomized clinical trial. Setting: Tertiary health center. Subjects and Methods: We randomly assigned 60 patients with otosclerosis planned for primary stapedotomy to receive either DLS or CMS. Primary outcome measure was hearing gain measured by pure-tone audiometry (PTA) performed preoperatively and postoperatively. Hearing gain was compared within and between the groups. Secondary outcome measures were the incidence of intraoperative (bleeding and fractured footplate) and postoperative (vomiting, vertigo, sensorineural hearing loss, tinnitus, facial nerve paralysis, and hospital stay) morbidities. Results: Sixty primary stapedotomies (30 in the CMS group and 30 in the DLS group) done for 60 patients (male, n = 42; female, n = 18) were included in the analysis. Preoperative mean air-bone (AB) gap in the DLS and CMS groups was 38.51 ± 8.643 dB and 36.42 ± 8.678 dB, respectively. Mean AB gap at 6 month was 10.86 ± 5.383 dB and 11.05 ± 5.236 dB in the CMS and DLS groups, respectively. Air conduction was improved by 24.98 ± 5.348 dB in the DLS group and 24.08 ± 5.911 dB in the CMS group at 6 months. No statistically significant differences were found in hearing gain between the 2 groups at 6 months ( P > .05). A decreased rate and severity of intraoperative bleeding, postoperative vertigo, and vomiting were observed with the diode laser (0%, 6.6%, and 10%) compared with the conventional technique (16.7%, 16.7%, and 16.7%), but these differences were not statistically significant ( P > .05). Conclusion: Hearing outcomes and complications of DLS were similar to CMS. These study findings confirm the efficacy of the diode laser in stapedotomy, but DLS offers no advantages over CMS for otosclerosis surgery.